BENCHMARKING AND CONFIGURATION OF OPENSOURCE MANUFACTURING EXECUTION SYSTEM (MES) APPLICATION - Ganesha Nur Laksmana; Prianggada Indra Tanaya; Yuki Indrayadi (Bina Nusantara University, 2013)
Information now is an important element to every growing industry in the world. Inorder to keep up with other competitors, endless improvements in optimizing overall efficiency areneeded. There still exist barriers that separate departments in PT. XYZ and cause limitation to theinformation sharing in the system. Open-Source Manufacturing Execution System (MES) presentsas an IT-based application that offers wide variety of customization to eliminate stovepipes bysharing information between departments. Benchmarking is used to choose the best Open-SourceMES Application; and Dynamic System Development Method (DSDM) is adopted as this workguideline. As a result, recommendations of the chosen Open-Source MES Application arerepresented.Keywords: Manufacturing Execution System (MES); Open Source; Dynamic SystemDevelopment Method (DSDM); Benchmarking; Configuration